Unique or not unique? Comparative genetic analysis of bacterial O-antigens from the Oxalobacteraceae family - S. D. Afonnikova; A. S. Komissarov; P. D. Kuchur (Вавиловский журнал генетики и селекции)
Many plants and animals have symbiotic relationships with microorganisms, including bacteria. The interactions between bacteria and their hosts result in different outcomes for the host organism. The outcome can be neutral, harmful or have beneficial effects for participants. Remarkably, these relationships are not static, as they change throughout an organism’s lifetime and on an evolutionary scale. One of the structures responsible for relationships in bacteria is O-antigen. Depending on the characteristics of its components, the bacteria can avoid the host’s immune response or establish a mutualistic relationship with it. O-antigen is a key component in Gram-negative bacteria’s outer membrane. This component facilitates interaction between the bacteria and host immune system or phages. The variability of the physical structure is caused by the genomic variability of genes encoding O-antigen synthesis components. The genes and pathways of O-polysaccharide (OPS) synthesis were intensively investigated mostly for Enterobacteriaceae species. Considering high genetic and molecular diversity of this structure even between strains, these findings may not have caught the entire variety possibly presented in non-model species. The current study presents a comparative analysis of genes associated with O-antigen synthesis in bacteria of the Oxalobacteraceae family. In contrast to existing studies based on PCR methods, we use a bioinformatics approach and compare O- anti gens at the level of clusters rather than individual genes. We found that the O-antigen genes of these bacteria are represented by several clusters located at a distance from each other. The greatest similarity of the clusters is observed within individual bacterial genera, which is explained by the high variability of O-antigens. The study describes similarities of OPS genes inherent to the family as a whole and also considers individual unique cases of O-antigen genetic variability inherent to individual bacteria.